2015
DOI: 10.1016/bs.acr.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Lymphoid Organogenesis in the Tumor Microenvironment

Abstract: The inflammatory status of the tumor microenvironment (TME) has been heavily investigated in recent years. Chemokine and cytokine signaling pathways such as CCR7, CXCR5, lymphotoxin, and IL-36, which are involved in the generation of secondary lymphoid organs and effector immune responses, are now recognized as having value both as prognostic factors and as immunomodulatory therapeutics in the context of cancer. Furthermore, when produced in the TME, these mediators have been shown to promote the recruitment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 122 publications
1
44
0
Order By: Relevance
“…In that context, in addition to the importance mentioned above of the Th17‐related cytokines (IL‐17, IL‐22, IL‐23) and the Tfh‐produced IL‐21, available data suggest that a number of other “positive regulators” contribute to ELS formation. For example, IL‐36 agonists, members of the IL‐1 sub‐family of cytokines together with IL‐1α, IL‐1β, IL‐18, and IL‐33, have indeed recently emerged as novel promoters of ELS generation in inflamed and neoplastic tissues . This effect likely depends on the IL‐36‐mediated ability to induce proinflammatory cytokines and chemokines that in turn recruit B/T lymphocytes and differentiate Th1 and IL‐17‐producing T cells …”
Section: Regulatory Mechanisms Of the Eln: The Key Role Of Homeostatimentioning
confidence: 99%
See 2 more Smart Citations
“…In that context, in addition to the importance mentioned above of the Th17‐related cytokines (IL‐17, IL‐22, IL‐23) and the Tfh‐produced IL‐21, available data suggest that a number of other “positive regulators” contribute to ELS formation. For example, IL‐36 agonists, members of the IL‐1 sub‐family of cytokines together with IL‐1α, IL‐1β, IL‐18, and IL‐33, have indeed recently emerged as novel promoters of ELS generation in inflamed and neoplastic tissues . This effect likely depends on the IL‐36‐mediated ability to induce proinflammatory cytokines and chemokines that in turn recruit B/T lymphocytes and differentiate Th1 and IL‐17‐producing T cells …”
Section: Regulatory Mechanisms Of the Eln: The Key Role Of Homeostatimentioning
confidence: 99%
“…CCL21, instead, is predominantly produced in the lymphatic vessels . Overall, a more favorable outcome has been observed in patients with solid cancers, for example, breast cancer, colorectal carcinomam, melanoma, and non‐small cell lung cancer characterized by the presence of ELS within the neoplastic tissue …”
Section: Cancer: New Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting mechanism through which ILC may influence tumor development is by their role in the formation of tertiary lymphoid structures (TLS). It has been shown that the proinflammatory features of the TME lead to the activation of chemokine signaling pathways and the recruitment of immune cells that contribute to the formation of TLS [85]. TLS are ectopic and highly organized lymphoid formations that develop in inflamed and infected tissues or within or adjacent to primary tumors.…”
Section: Effector Mechanisms Of Ilc In Cancermentioning
confidence: 99%
“…Additionally, although conventional DC-based vaccines are thought to cross-prime specific T-cell responses in vaccine site-draining lymph nodes, DCs injected directly into tumor lesions under certain conditions may nucleate the formation of tertiary lymphoid structures (TLS) in the TME where tumor antigen-specific T-cell priming may occur. TLS are a lymph node-like organized network of innate and adaptive cells that act as sites of adaptive immune induction and these can be found in the TME, where they have generally been associated with improved clinical prognosis [74,75]. We have previously reported that intratumoral delivery of DC engineered to express the Type I activator T-bet (DC.Tbet) promotes the active recruit of immune cells into TLS, leading to specific T-cell induction and slowed tumor growth in the murine MCA205 sarcoma model [76].…”
Section: Future Perspectivementioning
confidence: 99%